Fever of Unknown Origin in an 18-year-old Boy - Hossain, Zazeba; Hannan, Tabiha Binte; Quraishi, Md Soabraj Al; Rahman, Md Sadiqur; Alam, Md Rafiqul; Chowdhury, Fazle Rabbi (Journal of Medicine, 2022)
Cardiac myxoma is a rare cause of fever of unknown origin. Typically, it presents with one or more ofthe triad namely constitutional, obstructive or embolic phenomenon. Rapid detection and earlysurgical resection is the only effective modality of treatment to prevent debilitating complicationsand mortality. Herein, we showcased a case presenting to us with fever and weight loss. High indexof suspicion and early transthoracic echocardiography is needed to avoid delayed diagnosis andunnecessary tests. J MEDICINE 2022; 23: 101-103